2019
DOI: 10.1111/dar.12893
|View full text |Cite
|
Sign up to set email alerts
|

Non‐medical use of pharmaceutical opioids with and without other illicit substances in Australia: Prevalence and correlates

Abstract: Introduction and Aims To estimate the prevalence of non‐medical use of pharmaceutical opioids and examine the socio‐demographic, psychological, health and behavioural correlates and type of opioids used. Design and Methods Data from the Australian National Drug Strategy Household Survey 2016 was used. The sample consisted of. 23 448 participants aged over 14 years (54% female). The key measure was opioid use status in the past year. Based on participants’ responses to questions about their substance use in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“… 42 - 44 , 66 , 67 In addition, some authors insist on the importance of understanding factors that contribute to regional differences in opioid use, such as culture, practices and regulations. 7 , 68 In line with their work, this review supports a better understanding of how local factors like socioeconomic contexts, local illegal drug markets and public health policies shape different profiles of people who have problematic opioid use and their associated needs. This understanding may be key to adapting the service offer to specific needs.…”
Section: Discussionsupporting
confidence: 58%
“… 42 - 44 , 66 , 67 In addition, some authors insist on the importance of understanding factors that contribute to regional differences in opioid use, such as culture, practices and regulations. 7 , 68 In line with their work, this review supports a better understanding of how local factors like socioeconomic contexts, local illegal drug markets and public health policies shape different profiles of people who have problematic opioid use and their associated needs. This understanding may be key to adapting the service offer to specific needs.…”
Section: Discussionsupporting
confidence: 58%
“…Literature suggests that most people use these medicines appropriately [25]. By analyzing the data of the latest round of the National Drug Strategy Household Survey, Chan and colleagues [26] found that in Australia the overall prevalence of past year non-medical pharmaceutical opioid use was 3.56%. Given that there is a demand for reducing untreated pain, and there exists a strong correlation between the quantity dispensed/the user numbers and the likelihood of inappropriate use, the public health measures mainly aim to reduce the inappropriate dispensing/utilization without hampering access for those who are duly in need to these medicines [27].…”
Section: Discussionmentioning
confidence: 99%
“…recreational use) (e.g. Chan et al, 2019) and/or 'in a way other than prescribed' (e.g. Faraone et al, 2020).…”
Section: Introductionmentioning
confidence: 99%